Uptake of validated technologies and processes to enhance land use planning, management, governance and restoration practices in mediterranean Silvopastoral systems- MELIA study - Louhaichi, Mounir; Hassan, Sawsan; Ouled Belgacem, Azaiez; Ben Haha, Med Naoufel (International Center for Agricultural Research in the Dry Areas, 2024)
This is a MELIA study conducted by a collaborative initiative involving ICARDA and the Directorate General of Forests in Tunisia, addressing the challenges faced by Tunisia's rangelands, which are vital for the livelihoods of many rural communities. The study highlighted significant improvements in livestock performance, ecosystem health, and community empowerment through silvopastoral interventions, such as reseeding with native forage legumes, optimized grazing practices, and capacity-building initiatives. Key findings indicated increased forage production, higher livestock weights, and enhanced milk production, contributing to both economic benefits for farmers and improved ecological sustainability in silvopastoral landscapes. The MELIA study emphasized the importance of evidence-based, community-centered approaches in sustainably managing Tunisia's silvopastoral resources.